2000
DOI: 10.1523/jneurosci.20-14-05292.2000
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Interleukin-1β and Tumor Necrosis Factor α Signaling by P2 Purinergic Receptors in Human Fetal Astrocytes

Abstract: In human astrocytes, interleukin-1beta (IL-1beta) is a potent inducer of genes associated with inflammation. In this study, we tested the hypothesis that in primary cultures of human fetal astrocytes signaling by the P2 purinergic nucleotide receptor pathway contributes to, or modulates, cytokine-mediated signal transduction. Calcium imaging studies indicated that most cells in culture responded to ATP, whereas only a subpopulation responded to UTP. Pretreatment of astrocytes with P2 receptor antagonists, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 51 publications
7
56
0
Order By: Relevance
“…However, activated lymphocytes, macrophages, microglia, and platelets, as well as cells undergoing necrosis or apoptosis, release high concentrations of different nucleotide diphosphates and triphosphates into the extracellular space (Dubyak and el-Moatissim, 1993). Using chemical antagonists, we recently found that autocrine or paracrine activity of extracellular nucleotides on P2 receptors is required for astrocyte activation (Liu et al, 2000), and similar findings have also been reported in murine macrophages (Hu et al, 1998;Sikora et al, 1999). In the present study, we tested the hypothesis that increased concentrations of extracellular nucleotides regulate IL-1␤ signal transduction in human astrocytes via a P2 receptormediated pathway.…”
Section: Abstract: P2 Receptors; Il-1␤; Human Fetal Astrocytes; Transupporting
confidence: 70%
See 2 more Smart Citations
“…However, activated lymphocytes, macrophages, microglia, and platelets, as well as cells undergoing necrosis or apoptosis, release high concentrations of different nucleotide diphosphates and triphosphates into the extracellular space (Dubyak and el-Moatissim, 1993). Using chemical antagonists, we recently found that autocrine or paracrine activity of extracellular nucleotides on P2 receptors is required for astrocyte activation (Liu et al, 2000), and similar findings have also been reported in murine macrophages (Hu et al, 1998;Sikora et al, 1999). In the present study, we tested the hypothesis that increased concentrations of extracellular nucleotides regulate IL-1␤ signal transduction in human astrocytes via a P2 receptormediated pathway.…”
Section: Abstract: P2 Receptors; Il-1␤; Human Fetal Astrocytes; Transupporting
confidence: 70%
“…Culture purity was determined by immunostaining for glial fibrillary acidic protein (astrocytes), microtubule-associated protein-2 (neurons), and CD68 (microglia). Recombinant human IL -1␤ was a gift from the Biological Response Modifiers Program at the National C ancer Institute (Frederick, MD); the dose used (10 ng /ml) was based on dose -response studies that we have performed previously on IL -1-mediated signal transduction in human fetal astrocytes (Liu et al, 2000). It is identical to that used in studies that have examined the IL -1 signaling cascade leading to N F-B and AP-1 activation in several other cell types (Delhase et al, 1999;NinomiyaTsuji et al, 1999).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Confirming this possibility, the blockade of the P2 receptors by PPADS may lead to a decrease of the NO release, an effect that is synergistic with the action of NOS inhibitors. Further evidence for a close relationship between P2 receptors and NO production is given by a study of Liu et al (2000), which shows that pretreatment of astrocytes with P2 receptor antagonists including PPADS results in a down regulation of interleukin-1b-stimulated NOS expression.…”
Section: Discussionmentioning
confidence: 99%
“…V␦2 ϩ T cells (5 ϫ 10 6 ) were stimulated in 24-well plates for 1 h with medium alone or 50 U/ml IL-2, IPP2X, or IPP2X in the presence of curcumin at 30 M. Nuclear extracts were prepared by a modified Dignam method on ice, and EMSA was performed as described previously (23). Oligonucleotides containing the NF-B consensus binding sequence (5Ј-AGT TGA GGG GAC TTT CCC AGG C-3Ј) or the AP-1 consensus binding sequence (5Ј-CGC TGG ATG AGT CAG CCG GAA-3Ј) were radiolabeled with [␥-32 P]ATP using polynucleotide T4 kinase (Gel Shift Assay Core System kit; Promega, Madison, WI).…”
Section: Emsamentioning
confidence: 99%